Interlinking technical assistance and coffee markets in fragmented value chains: Experimental design and baseline survey report - Ceballos-Sierra, Federico; Igeler, William; Wiegel, Jennifer; Reyes, Byron A.; Espada, Andrés (International Food Policy Research Institute, 2023)
This document offers an analysis of a pilot program aimed at improving productivity and sup ply chain integration for small-scale coffee farmers. It details the collaboration between a ma jor coffee exporter, local intermediaries, and farmers, introducing a unique stepped-wedge cluster randomized trial for program evaluation. The report covers the findings from a base line survey, including in-depth sociodemographic data, coffee farming practices, and other vi tal metrics. The survey's results illuminate the current state of coffee farming in the Santa Bar bara region of Honduras, providing critical insights for future interventions. The document concludes by discussing the policy implications and challenges faced during the implementa tion of this program, offering valuable lessons for similar future initiatives.